Pharmaceutical container, pharmaceutical container manufacturing method and coating agent
Patent Information
- Application Number
- JP2022507169
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-16
- Filing Date
- 2021-03-08
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2041-03-08
AI Technical Summary
【0032】 本発明によれば、環境負荷が低く、取り扱いが容易であり、且つ撥水性が高い医薬品容器を提供することができる。
Smart Images

Figure 0007636726000001 
Figure 0007636726000002 
Figure 0007636726000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pharmaceutical container having good water repellency and resistance to preparations with a wide range of pH levels, a manufacturing method for the pharmaceutical container, and a coating agent. Specifically, the present invention relates to a pharmaceutical container in which a coating layer containing a silicone-based resin is applied to at least the inner surface of the container, a manufacturing method thereof, and a coating agent containing a silicone-based resin. [Background technology]
[0002] Pharmaceutical containers such as vials and ampoules require high chemical durability to stably store pharmaceutical preparations, and therefore use borosilicate glass, which has excellent chemical resistance.
[0003] In addition, pharmaceutical containers are washed using a water jet, washed with detergent, ultrasonically washed, etc. before being filled with the formulation. Furthermore, dry heat sterilization at about 300°C is performed to inactivate pyrogens. Therefore, it is important that pharmaceutical containers do not change, deteriorate, peel, etc. even after undergoing the washing process and dry heat sterilization. In particular, it is important that no change, deterioration, peeling, etc. occurs even when formulations of various pH levels are filled into the containers.
[0004] Patent Document 1 proposes a method for improving the water repellency, water resistance, and alkali resistance of a glass container by forming a fluororesin coating layer on the inner surface of the container. However, this coating layer contains fluorine, which causes problems in terms of environmental impact and handling.
[0005] Patent Document 2 proposes a method for improving the water repellency of a glass container by forming a fluorine-containing coating layer on the inner surface of the container, and further a method for reducing the amount of Si elution when the container is filled with water and autoclaved. However, this coating layer contains fluorine, which poses problems in terms of environmental impact and handling. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2013 / 179514 [Patent Document 2] Japanese Patent Application Publication No. 5-132065 Summary of the Invention [Problem to be solved by the invention]
[0007] The glass surface of borosilicate glass is very hydrophilic, which can cause, for example, the following problems:
[0008] It is necessary to reliably administer a prescribed dosage to a patient with an injectable drug. However, if the glass surface is highly hydrophilic, liquid may remain on the inner surface of the container, making it impossible to administer the appropriate amount. This is a very serious problem, and in order to solve this, the current situation is that the formulation is filled in excess of the appropriate amount, taking into account the amount of residue in advance. As a result, more than the appropriate amount of formulation is administered, and formulation costs increase.
[0009] In addition, biopharmaceuticals, which have been developed in recent years, are known to be very unstable and to be altered by external factors such as temperature fluctuations and vibrations. For this reason, liquid agents are freeze-dried. However, if the glass surface is highly hydrophilic, the liquid agent in the container rises to the body of the container during the freeze-drying process, and becomes cloudy after freeze-drying, which can cause problems such as reduced visibility and appearance of the container.
[0010] In order to solve the above problems, it is effective to form a coating layer on the inner surface of the container. However, as described above, current coating layers contain halogen components such as fluorine components, which poses problems in terms of environmental impact and handling.
[0011] Therefore, an object of the present invention is to provide a pharmaceutical container that has a low environmental impact, is easy to handle, and has high water repellency, and a method for producing the same, and to provide a coating agent that enhances the water repellency of the coating layer. [Means for solving the problem]
[0012] The inventors conducted various experiments and found that the above technical problems can be solved by coating the inner surface of the container with a coating layer containing a silicone-based resin, and propose this as the present invention. That is, the pharmaceutical container of the present invention is a pharmaceutical container comprising at least a container and a coating layer, characterized in that the coating layer is formed on at least the inner surface of the container, and the coating layer contains a silicone-based resin.
[0013] In addition, in the pharmaceutical container of the present invention, the silicone-based resin is preferably an organopolysiloxane compound having one or more organic substituents selected from the group consisting of a methyl group, a phenyl group, an epoxy group, an ether group, and a polyester group. The pH of the formulation is designed to be about pH 6 to 8 so as not to cause pain or numbness during administration. However, some types of formulations exhibit acidity or alkalinity, such as pH 4 or pH 11. Although borosilicate glass has a certain degree of resistance to acidic solutions, it is easily eroded by alkaline solutions. Therefore, if the pH of the formulation becomes high, there is a risk that the glass component of the container will dissolve and cause deterioration of the formulation. Therefore, by introducing the above silicone-based resin into the coating agent, good water repellency can be maintained even when formulations of a wide range of pH are filled in the container and stored for a long period of time, and deterioration and peeling of the coating layer can be suppressed.
[0014] In addition, in the pharmaceutical container of the present invention, it is preferable that the coating layer is substantially free of halogen components. Here, "substantially free of halogen components" means that the content of halogen components in the coating layer is less than 0.8% by mass.
[0015] In addition, in the pharmaceutical container of the present invention, the thickness of the coating layer is preferably 10 to 2500 nm, which makes it difficult for defects such as pinholes to occur and reduces stress generated after thermal curing, thereby suppressing deterioration, peeling, etc. of the coating layer.
[0016] In addition, in the pharmaceutical container of the present invention, the container is made of silicate glass, and the silicate glass preferably contains, in mass %, 65-85% SiO2, 0-15% Al2O3, 0-13% B2O3, 0-5% Li2O, 3-15% Na2O, 0-5% K2O, 0-5% MgO, 0-15% CaO, and 0-5% BaO as a glass composition, which can enhance the chemical resistance of the container while maintaining the workability into the container shape.
[0017] In the pharmaceutical container of the present invention, when filled with purified water and subjected to a heat treatment at 121° C. for 180 minutes, the amount of silicon eluted is preferably 40 μg / mL or less, more preferably 35 μg / mL or less, further preferably 25 μg / mL or less, and particularly preferably 15 μg / mL or less. If the amount of silicon eluted is large, there is a risk that the silicon will be reprecipitated in the solvent and become an insoluble foreign matter.
[0018] In the pharmaceutical container of the present invention, when filled with a 3 mass% citric acid aqueous solution of pH 8 and subjected to heat treatment at 121°C for 180 minutes, it is preferable that the relationship X / Y≦10, further X / Y≦7, and particularly X / Y≦5 is satisfied, where the amount of Si eluted is X μg / mL and the thickness of the coating layer is Y nm.
[0019] In the pharmaceutical container of the present invention, the bottom area of the container is S cm 2 A volume (ml) of purified water equivalent to 0.1 × 0.01 is dropped onto the bottom of the container, the container is then turned left and right, then turned upright, and then placed horizontally. The bottom area S′ covered by the purified water is then calculated as the bottom area Scm 2 It is preferably 90% or less, more preferably 85% or less, and even more preferably 80% or less.
[0020] The container of the present invention is provided with at least a coating layer. 2A volume (ml) of purified water equivalent to 0.1 × 0.01 is dropped onto the bottom of the container, the container is then turned left and right, then turned upright, and then placed horizontally. The bottom area S′ covered by the purified water is then calculated as the bottom area Scm 2 It is preferably 90% or less, and particularly preferably 85% or less.
[0021] The method for manufacturing a pharmaceutical container of the present invention is characterized in that it comprises at least a container and a coating layer, and includes the steps of preparing a container made of silicate glass or resin, applying a coating agent containing a silicone-based resin to at least the inner surface of the container, and thermally curing the applied coating agent to form a coating layer.
[0022] In the method for producing a pharmaceutical container of the present invention, the coating agent preferably contains an organic acid.
[0023] In the method for producing a pharmaceutical container of the present invention, the organic acid is preferably one or more selected from the group consisting of amino acids, citric acid, acetic acid, and oxalic acid.
[0024] In the method for producing a pharmaceutical container of the present invention, the thickness of the coating layer is preferably 10 to 2500 nm, which makes it difficult for defects such as pinholes to occur and reduces stress generated after thermal curing, thereby suppressing deterioration, peeling, etc. of the coating layer.
[0025] The coating agent of the present invention is a coating agent for forming a coating layer on a glass surface or a resin surface (particularly the inner surface of a pharmaceutical container), and is characterized by containing an organopolysiloxane compound having one or more organic substituents selected from the group consisting of methyl groups, phenyl groups, epoxy groups, ether groups, and polyester groups. By introducing the organopolysiloxane compound having the organic substituents, the coating layer can maintain good water repellency even when in contact with a preparation having a wide range of pH levels for a long period of time, and deterioration, peeling, etc. of the coating layer can be suppressed.
[0026] The coating agent of the present invention is a coating agent for forming a coating layer on the inner surface of a pharmaceutical container, and is characterized by containing an organopolysiloxane compound having one or more organic substituents selected from the group consisting of methyl groups, phenyl groups, epoxy groups, ether groups, and polyester groups. By introducing the organopolysiloxane compound having the organic substituents, the coating layer formed on the inner surface of the pharmaceutical container can maintain good water repellency even when in contact with preparations of a wide range of pH levels for a long period of time, and deterioration, peeling, etc. of the coating layer can be suppressed.
[0027] In addition, it is preferable that the coating agent of the present invention is substantially free of halogen components.
[0028] In addition, in the coating agent of the present invention, the content of the organopolysiloxane compound is preferably 1 to 50 mass %, which makes it easier to adjust the viscosity of the coating agent and to make the thickness of the coating layer uniform.
[0029] In the coating agent of the present invention, the organopolysiloxane compound contains dimethylpolysiloxane, phenylpolysiloxane, and methylpolysiloxane, and when the molar ratios of dimethylpolysiloxane:phenylpolysiloxane:methylpolysiloxane=A:B:C, it is preferable that A is 0.1 to 4.0, B is 0.1 to 4.0, and C is 0.1 to 4.0.
[0030] In addition, the coating agent of the present invention preferably further contains one or more organic acids selected from the group consisting of citric acid, amino acids, acetic acid, and oxalic acid.
[0031] In the coating agent of the present invention, the content of the organic acid is preferably 0.1 to 10% by mass. Effect of the Invention
[0032] According to the present invention, it is possible to provide a pharmaceutical container that has a low environmental impact, is easy to handle, and has high water repellency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] Hereinafter, preferred embodiments of a pharmaceutical container and a method for manufacturing the same will be described. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments.
[0034] [Coating agent] The coating agent (coating layer) for forming the coating layer contains a silicone resin, particularly an organopolysiloxane compound, and preferably has one or more organic substituents selected from the group consisting of methyl groups, phenyl groups, epoxy groups, ether groups, and polyester groups in its molecule. By introducing an organopolysiloxane compound having the above organic substituents, the coating layer can maintain good water repellency even when in contact with preparations of a wide range of pH levels for a long period of time, and can suppress deterioration, peeling, etc. of the coating layer.
[0035] The organopolysiloxane compound contains at least one siloxane structure. The siloxane structure is as shown below, and may be a composite structure consisting of a single chain, a chain, and a cage structure, and the side chain R represents a hydrogen atom or a hydrocarbon group. Polymerized siloxanes consisting of oligomer and polymer siloxane units having organic side chains (R≠H) are represented as polysiloxanes (SiOR1R2)n (n≧1), where R1 and R2 have one or more organic substituents selected from the group consisting of methyl groups, phenyl groups, epoxy groups, ether groups, and polyester groups.
[0036] [ka] [ka]
[0037] Representative examples of polysiloxanes are shown below. Methylpolysiloxane: (SiO(CH4))n (n ≥ 1) Phenylpolysiloxane: (SiO(C6H6)) n (n ≥ 1) Dimethylpolysiloxane: (SiO(CH3)2) n (n ≥ 1) [ka] [ka] [ka]
[0038] The content of the silicone resin, particularly the organopolysiloxane compound, in the coating agent is, by mass%, preferably 1% or more, 5% or more, 10% or more, particularly preferably 15% or more, and preferably 50% or less, 45% or less, particularly preferably 40% or less. If the content of the silicone resin, particularly the organopolysiloxane compound, is too high, the viscosity of the coating agent increases, making it difficult to apply the coating to the inner surface of the container with a uniform thickness, and as a result, cracks and peeling are likely to occur due to residual stress in the coating layer during drying and heat curing.
[0039] The organopolysiloxane compound contained in the coating agent preferably contains dimethylpolysiloxane, phenylpolysiloxane, and methylpolysiloxane. By containing these, it is possible to increase water repellency and improve stability against temperature. When the molar ratio is dimethylpolysiloxane:phenylpolysiloxane:methylpolysiloxane=A:B:C, A is 0.1-4.0, B is 0.1-4.0, C is 0.1-4.0, preferably A is 0.3-3.0, B is 0.4-2.5, C is 0.4-2.5, more preferably A is 0.6-2.0, B is 0.7-1.5, C is 0.7-1.5. If the mass ratio of both is outside the above range, it becomes difficult to sufficiently increase water repellency and the thermal stability against temperature is impaired.
[0040] The coating agent is preferably applied to the inner surface of the container in a state where it is uniformly mixed with an organic solvent. The organic solvent is not particularly limited, but examples thereof include butyl alcohol, isopropyl alcohol, isopropyl acetate, and the like. These organic solvents may be used in combination, or only one type may be used. The content of the organic solvent in the coating agent is preferably 1% or more, 5% or more, 10% or more, 15% or more, 20% or more, particularly 25% or more, and is preferably 80% or less, 60% or less, particularly 40% or less, by mass%.
[0041] The coating agent may contain a surface conditioner for adjusting the surface tension. This can increase the smoothness of the coating layer after application to the inner surface of the container. The content of the surface conditioner in the coating agent is, in mass %, preferably 0 to 10%, more preferably 0 to 5%, and particularly preferably 0.5 to 1%.
[0042] The coating agent preferably further contains an organic acid such as amino acid, citric acid, acetic acid, or oxalic acid. This allows the coating agent to maintain excellent chemical resistance even against high pH solutions. A mixture of multiple types of organic acids may be used, or only one type may be used. The content of the organic acid in the coating agent is preferably 0.1% or more, 0.5% or more, and particularly preferably 1% or more, and is preferably 10% or less, 8% or less, 5% or less, and particularly preferably 4% or less, in mass %. If the content of the organic acid is too high, the coating agent may corrode the surface of the container when applied.
[0043] It is preferable that the coating agent (coating layer) is substantially free of halogen components, particularly fluorine components and chlorine components, which can reduce the environmental load and improve the ease of handling.
[0044] The peak intensity of the Raman spectrum of the coating layer is in the wavenumber range of 900 to 1250 cm -1 , 1500~1650cm -1 , 2500~3000cm -1In each case, it is preferable that the value is 1.1 times or more of the base value when fitting processing is performed with a Gaussian function. This makes it possible to maintain good water repellency and suppress deterioration and peeling of the coating layer even when a formulation with a wide range of pH is filled in a container and stored for a long period of time.
[0045] [How to apply coating agent] In order to apply the coating agent uniformly, it is preferable to wash the container in advance. The washing method is not particularly limited, but may be, for example, removing dust by air blowing or washing with a solvent such as purified water or acetone.
[0046] The method for applying the coating agent is not particularly limited, and a dipping method, a spraying method, an electrostatic spraying method, or the like can be applied.
[0047] [Formation of coating layer] It is preferable to apply the coating agent to the inner surface of the container, and then dry and heat-cure the coating layer. The drying step is a step for volatilizing the organic solvent in the coating agent. The heat-cure step is a step for subjecting the coating agent to a dehydration condensation reaction to firmly bond the coating agent to the inner surface of the container.
[0048] The drying temperature in the drying step is preferably 40° C. or higher, 45° C. or higher, particularly preferably 50° C. or higher, and is preferably 180° C. or lower, 170° C. or lower, particularly preferably 150° C. or lower. If the drying temperature is too low, the organic solvent is not sufficiently removed from the coating agent, and the coating layer is likely to become cloudy or peel off. If the drying temperature is too high, a thermosetting reaction occurs, and the coating layer is likely to become cloudy or peel off.
[0049] The drying time is preferably 5 minutes or more, 10 minutes or more, 15 minutes or more, particularly 20 minutes or more, and is preferably 120 minutes or less, 100 minutes or less, particularly 80 minutes or less. If the drying time is too short, the organic solvent is not sufficiently removed from the coating agent, and the coating layer is likely to become cloudy or peel off. If the drying time is too long, the productivity of the pharmaceutical container decreases.
[0050] The heat curing temperature in the heat curing step is preferably 185°C or higher, 190°C or higher, particularly 200°C or higher, and preferably 450°C or lower, 400°C or lower, particularly 350°C or lower. If the heat curing temperature is too low, the heat curing reaction does not occur sufficiently, making it difficult to increase the water repellency of the pharmaceutical container. On the other hand, if the heat curing temperature is too high, the coating agent may be thermally decomposed, causing defects in the coating layer, and in the worst case, the coating layer may disappear.
[0051] The heat curing time is preferably 5 minutes or more, 10 minutes or more, particularly 15 minutes or more, and is preferably 150 minutes or less, 140 minutes or less, particularly 120 minutes or less. If the heat curing time is too short, the heat curing reaction does not occur sufficiently, making it difficult to increase the water repellency of the pharmaceutical container. On the other hand, if the heat curing time is too long, the productivity of the pharmaceutical container decreases.
[0052] The thickness of the coating layer after heat curing is preferably 10 nm or more, 20 nm or more, 50 nm or more, 100 nm or more, 120 nm or more, 300 nm or more, 500 nm or more, 520 nm or more, and preferably 2500 nm or less, 2000 nm or less, particularly preferably 1500 nm or less, which makes it difficult for defects such as pinholes to occur and reduces stress generated after heat curing, thereby suppressing deterioration, peeling, etc. of the coating layer.
[0053] [container] From the viewpoint of chemical resistance, the container is preferably made of glass, particularly silicate glass. The silicate glass preferably contains, by mass%, SiO2 65-85%, Al2O3 0-15%, B2O3 0-13% (preferably 1-13%), Li2O 0-5%, Na2O 3-15%, K2O 0-5%, BaO 0-5%, CaO 0-15%, and MgO 0-5%. It is also preferable that the container contains, by mass%, SiO2 65-85%, Al2O3 1-15%, B2O3 0-13% (preferably 1-13%), Na2O 3-15%, K2O 0-5%, BaO 0-5%, CaO 0-5%, and MgO 0-5%. The container may be brown in color to block ultraviolet rays. That is, it may contain 0.001 to 5% Fe2O3 and 0.001 to 5% TiO2 by mass%. In addition, in the case of a glass container, SnO2, Sb2O3, As2O3, CeO2, F, Cl, Glauber's salt, etc. may be contained as a clarifier. The content of these is not particularly limited, but from the viewpoint of production cost and environmental load, the individual content or total content is preferably 0% or more, 0.001% or more, 0.002% or more, 0.005% or more, 0.007% or more, and 2% or less, 1.8% or less, 1.5% or less, 1% or less, 0.8% or less, 0.5% or less, 0.3% or less. From the viewpoint of processability into a container shape, the container is preferably made of resin, particularly polypropylene, polyethylene, polyethylene terephthalate, polyvinyl chloride, cycloolefin polymer, cycloolefin copolymer, polymethylpentene, polycarbonate, etc.
[0054] The linear thermal expansion coefficient of silicate glass at 30 to 380°C is preferably 100×10 -7 / ℃ or less, 90×10 -7 / ℃ or less, 80×10 -7 / ℃ or less, 70×10 -7 / ℃ or less, 60×10 -7 / ℃ or less, 50×10 -7 / ℃ or less, 35×10 -7 / ℃ or more 45×10 -7 / ° C. or less. If the linear thermal expansion coefficient at 30 to 380° C. is restricted to the above range, the amount of Si elution is reduced. The linear thermal expansion coefficient at 30 to 380° C. can be measured by a dilatometer or the like.
[0055] On the other hand, if the silicate glass has a high linear thermal expansion coefficient at 30 to 380°C, the manufacturing efficiency of the pharmaceutical container increases, but on the other hand, the amount of Si elution increases, making it difficult to use as a pharmaceutical container. However, if the coating layer according to the present invention is formed, it can be used as a pharmaceutical container even in such a case. In other words, when the silicate glass has a high linear thermal expansion coefficient at 30 to 380°C, the effect of the present invention can be adequately enjoyed. In this case, the linear thermal expansion coefficient of the silicate glass at 30 to 380°C is preferably 25×10 -7 / ℃ or more, 30×10 -7 / ℃ or more, 40×10 -7 / ℃ or more, 50×10 -7 / ℃ or more, 60×10 -7 / ℃ or more, 70×10 -7 / ℃ or more, 80×10 -7 / ℃ or more 100×10 -7 / ℃ or less.
[0056] [Medicine containers] The pharmaceutical container of the present invention can be used in various forms, for example, a vial container, an ampoule container, a syringe, a cartridge, etc.
[0057] In the pharmaceutical container of the present invention, the recovery rate of purified water shown below after heat treatment at 121°C for 60 minutes or 180 minutes is preferably more than 95%. Using the pharmaceutical container after heat treatment at 121°C for 60 minutes or 180 minutes, a test for recovery rate of purified water is performed according to the following procedure. First, the mass of the container from which water droplets have been removed is measured and recorded using an electronic balance, and then the mass is measured in a state in which the pharmaceutical container is filled with purified water, and the mass of the pharmaceutical container is subtracted to calculate the "mass of filled purified water". Next, the pharmaceutical container filled with purified water is inverted, and the pharmaceutical container that has been emptied by draining the purified water is placed on the electronic balance again, and the mass is measured and recorded. The "mass of recovered purified water" is calculated by subtracting the mass of the pharmaceutical container after draining the water from the mass of the filled purified water. Finally, the recovery rate of the filled purified water is calculated using formula (1). Recovery rate (%) = {(mass of purified water recovered) / (mass of purified water filled)} × 100 (1)
[0058] In the pharmaceutical container of the present invention, when filled with a 3% by mass citric acid aqueous solution of pH 8 and subjected to heat treatment at 121°C for 180 minutes, the amount of Si eluted is X μg / mL and the thickness of the coating layer is Y nm, and it is preferable that X / Y is 10 or less, 9 or less, 7 or less, 6 or less, 5 or less, 4.5 or less, 4 or less, 3 or less, 2 or less, 1.5 or less, 1.2 or less, 1 or less, 0.7 or less, 0.5 or less, 0.3 or less, 0.1 or less, 0.07 or less, 0.05 or less, or 0.03 or less. If the value of X / Y is large, insoluble foreign matter is more likely to be generated in the pharmaceutical.
[0059] In the pharmaceutical container of the present invention, when filled with a 3% by mass citric acid aqueous solution of pH 8 and subjected to heat treatment at 121°C for 60 minutes, the amount of Si eluted is X'μg / mL and the thickness of the coating layer is Y nm, and it is preferable that X' / Y is 10 or less, 9 or less, 7 or less, 6 or less, 5 or less, 4.5 or less, 4 or less, 3 or less, 2 or less, 1.5 or less, 1.2 or less, 1 or less, 0.7 or less, 0.5 or less, 0.3 or less, 0.1 or less, 0.07 or less, 0.05 or less, or 0.03 or less. If the value of X' / Y is large, insoluble foreign matter is more likely to be generated in the pharmaceutical.
[0060] In the pharmaceutical container of the present invention, when filled with purified water and subjected to heat treatment at 121°C for 60 minutes, the amount of Si eluted is X'' μg / mL and the thickness of the coating layer is Y nm, then it is preferable that X'' / Y is 10 or less, 9 or less, 7 or less, 6 or less, 5 or less, 4.5 or less, 4 or less, 3 or less, 2 or less, 1.5 or less, 1.2 or less, 1 or less, 0.7 or less, 0.5 or less, 0.3 or less, 0.1 or less, 0.07 or less, 0.05 or less, or 0.03 or less. If the value of X'' / Y is large, insoluble foreign matter is more likely to be generated in the pharmaceutical.
[0061] In the pharmaceutical container of the present invention, the bottom area of the container is S cm 2 A volume of purified water V (ml) equivalent to 0.1 × 0.1 is dropped onto the bottom of the container, the container is then turned over, and the bottom area S′ covered by the purified water when it is placed horizontally is the bottom area Scm 2 It is preferable that the bottom area S' is 90% or less, 85% or less, 70% or less, 75% or less, 70% or less, 65% or less, 60% or less, 58% or less, 55% or less, 53% or less, and particularly 50% or less. If the bottom area S' is large, the water repellency will be low, and the amount of medicinal solution that can be taken out of the pharmaceutical container will be reduced, which may make it impossible to administer an appropriate amount of medicinal solution to a patient.
[0062] The water repellency test can be carried out by the following procedure. First, calculate the base area S of the container from the inside diameter r (cm) of the container using formula (2). Next, drip the volume of purified water V (mL) calculated using formula (3) into the container. After dripping the container, turn it sideways, then turn it back over and leave it horizontally to photograph the bottom of the container from below. The area S' (cm2) covered by the purified water relative to the base area S of the container is then calculated. 2 The area S' was calculated using the analysis software of a digital microscope VHX-500 (manufactured by Keyence Corporation). The area ratio (%) covered by purified water was calculated by dividing the bottom area S' by the bottom area S. The base area of the container S (cm 2 ) = inner diameter of container r / 2 (cm) × inner diameter of container r / 2 (cm) × pi (2) Amount of purified water to be dropped V (mL) = Bottom area of container S (cm 2 ) × 0.1 (3) EXAMPLES
[0063] The present invention will be described in detail with reference to examples. Note that the following examples are merely illustrative and the present invention is not limited to the following examples.
[0064] Tables 1 to 4 show examples of the present invention (samples Nos. 1 to 4, 6, and 9 to 38) and comparative examples (samples Nos. 5, 7, 8, and 39).
[0065] [Table 1]
[0066] [Table 2]
[0067] [Table 3]
[0068] [Table 4]
[0069] [Sample No. 1] A coating agent was prepared by mixing and dissolving 30% by mass of an organopolysiloxane compound (silicone resin) containing methyl and phenyl groups, 15% by mass of butyl alcohol, 10% by mass of isopropyl acetate, and 45% by mass of isopropyl alcohol, and then adding 2% by mass of citric acid, mixing and dissolving the mixture. The molar ratio of dimethylpolysiloxane, phenylpolysiloxane, and methylpolysiloxane contained in the organopolysiloxane compound was adjusted to 1.3:1:1.
[0070] A vial container with a volume of 10 mL was prepared by processing a borosilicate glass tube with an outer diameter of 20 mmφ and a wall thickness of 1 mm. The vial container was filled to the brim with the above-mentioned coating agent, and the vial was turned upside down to drain the coating agent, and then the vial was turned sideways so that the mouth of the vial was on the outside and spun in a centrifuge to remove the coating agent remaining in the vial container. The vial coated with the coating agent was dried for 60 minutes in a dryer heated to 60°C. Next, a heat curing treatment was performed for 60 minutes in a dryer heated to 210°C to 225°C. Next, the inside and outside of the vial container after the heat curing treatment were washed three times each with purified water, and then a hydrochloric acid aqueous solution adjusted to pH 4 was filled up to 90 volumes. Then, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and the internal liquid was prevented from leaking, and then heat treatment was performed in an autoclave at 121°C for 60 minutes.
[0071] [Sample No. 2] The vial container coated with the coating agent shown in Example 1 in the same manner was dried for 60 minutes in a dryer heated to 100°C. Next, heat curing treatment was performed for 120 minutes in a dryer heated to 225°C. Next, the inside and outside of the vial container after heat curing treatment were washed three times each with purified water, and then an aqueous sodium hydroxide solution adjusted to pH 11 was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then the internal liquid was prevented from leaking, and heat treatment was performed in an autoclave at 121°C for 60 minutes.
[0072] [Sample No. 3] A coating agent was prepared by mixing and dissolving 30% by mass of an organopolysiloxane compound (silicone resin) containing methyl groups and phenyl groups, 15% by mass of butyl alcohol, 10% by mass of isopropyl acetate, and 45% by mass of isopropyl alcohol. The molar ratio of dimethylpolysiloxane, phenylpolysiloxane, and methylpolysiloxane contained in the organopolysiloxane compound was adjusted to 1.3:1:1. A borosilicate glass tube (BS manufactured by Nippon Electric Glass Co., Ltd.) with an outer diameter of 20 mm and a wall thickness of 1 mm was processed to prepare a vial container with a volume of 10 mL. The vial container was filled to the brim with the above-mentioned coating agent, and the coating agent was discharged by inverting the vial, and the coating agent remaining in the vial container was removed by a centrifuge. The vial to which the coating agent was applied was dried for 60 minutes in a dryer heated to 60°C. Next, a heat curing treatment was performed for 60 minutes in a dryer heated to 210°C to 225°C. After the heat curing treatment, the vial container was taken out and cooled to room temperature. Next, the inside and outside of the vial container were washed three times each with purified water, and then an aqueous solution of sodium hydroxide adjusted to pH 11 was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and the container was rolled up, and after making sure that the liquid contained therein did not leak, the container was heat-treated in an autoclave at 121°C for 60 minutes.
[0073] [Sample No. 4] The inside and outside of the vial container that had been heat-cured in the same manner as in Example 2 were washed three times each with purified water, and then filled with an aqueous sodium hydroxide solution adjusted to pH 8 up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and the container was rolled up and then stored in a thermo-hygrostat set at 40°C and humidity 75% for three months after being made to prevent leakage of the internal solution.
[0074] [Sample No. 5] A 10 mL vial container machined from a borosilicate glass tube with an outer diameter of 20 mm and a wall thickness of 1 mm was washed inside and outside with purified water three times each, and then filled with an aqueous solution of sodium hydroxide adjusted to pH 8 up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and the container was rolled up and then stored in a constant temperature and humidity chamber at 40°C and 75% humidity for three months, after which the liquid inside was prevented from leaking.
[0075] [Sample No. 6] A 10 mL vial container machined from a borosilicate glass tube with an outer diameter of 20 mmφ and a wall thickness of 1 mm was subjected to a heat curing treatment in the same manner as in Example 2. Next, the inside and outside of the vial container after the heat curing treatment were washed three times each with purified water, and then an aqueous sodium hydroxide solution adjusted to pH 8 was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and the container was rolled up and then stored in a thermo-hygrostat set at 40°C and humidity of 75% for six months after the internal solution was prevented from leaking.
[0076] [Sample No. 7] A 10 mL vial container machined from a borosilicate glass tube with an outer diameter of 20 mm and a wall thickness of 1 mm was washed inside and outside with purified water three times each, and then filled with an aqueous solution of sodium hydroxide adjusted to pH 8 up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and the container was rolled up and then stored in a constant temperature and humidity chamber set at 40°C and a humidity of 75% for six months after the vial container was sealed to prevent leakage of the liquid.
[0077] [Sample No. 8] A 10 mL vial container machined from a borosilicate glass tube with an outer diameter of 20 mm and a wall thickness of 1 mm was washed inside and outside with purified water three times each, and then filled with 90 volumes of sodium hydroxide aqueous solution adjusted to pH 11. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up to prevent leakage of the internal liquid, and then heat-treated at 121°C for 60 minutes.
[0078] [Sample No. 9] The coating agent shown in Example 1 was applied to a 10 mL vial container machined from a borosilicate glass tube with an outer diameter of 20 mmφ and a wall thickness of 1 mm in the same manner, and dried for 60 minutes in a dryer heated to 100°C. Next, a heat curing treatment was performed for 60 minutes in a dryer heated to 250°C. After the heat curing treatment, the inside and outside of the vial container were washed three times each with purified water, and then an aqueous sodium hydroxide solution adjusted to pH 11 was filled up to 90 volumes. Then, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and the internal liquid was prevented from leaking, and then heat treatment was performed for 60 minutes at 121°C.
[0079] [Sample No. 10] The coating agent shown in Example 1 was applied to a 10 mL vial container machined from a borosilicate glass tube with an outer diameter of 20 mmφ and a wall thickness of 1 mm in the same manner, and dried for 60 minutes in a dryer heated to 100°C. Next, a heat curing treatment was performed for 30 minutes in a dryer heated to 275°C. After the heat curing treatment, the inside and outside of the vial container were washed three times each with purified water, and then an aqueous sodium hydroxide solution adjusted to pH 11 was filled up to 90 volumes. Then, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and the internal liquid was prevented from leaking, and then heat treatment was performed at 121°C for 60 minutes.
[0080] [Sample No. 11] The coating agent shown in Example 1 was applied to a 10 mL vial container machined from a borosilicate glass tube with an outer diameter of 20 mmφ and a wall thickness of 1 mm in the same manner, and dried for 60 minutes in a dryer heated to 100°C. Next, a heat curing treatment was performed for 15 minutes in a dryer heated to 300°C. After the heat curing treatment, the inside and outside of the vial container were washed three times each with purified water, and then an aqueous sodium hydroxide solution adjusted to pH 11 was filled up to 90 volumes. Then, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and the internal liquid was prevented from leaking, and then heat treatment was performed at 121°C for 60 minutes.
[0081] [Sample No. 12] The coating agent shown in Example 1 was applied to a 10 mL vial of solution processed from a borosilicate glass tube with an outer diameter of 22 mm and a wall thickness of 1 mm in the same manner, and heat curing treatment was performed for 30 minutes in a dryer heated to 275°C. After the heat curing treatment, the inside and outside of the vial container were washed with purified water three times each, and then the purified water was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then the internal liquid was prevented from leaking, and heat treatment was performed at 121°C for 180 minutes.
[0082] [Sample No. 13] The coating agent shown in Example 1 was applied to a vial containing 10 mL of solution processed from a borosilicate glass tube with an outer diameter of 22 mm and a wall thickness of 1 mm in the same manner, and heat curing treatment was performed for 30 minutes in a dryer heated to 275°C. After the heat curing treatment, the inside and outside of the vial container were washed three times each with purified water, and then a 0.9% by mass concentration KCl aqueous solution (pH adjusted to 8 with potassium hydroxide) was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then heat treatment was performed at 121°C for 180 minutes while preventing leakage of the internal liquid.
[0083] [Sample No. 14] The coating agent shown in Example 1 was applied to a vial containing 10 mL of solution processed from a borosilicate glass tube with an outer diameter of 22 mm and a wall thickness of 1 mm in the same manner, and heat curing treatment was performed for 30 minutes in a dryer heated to 275°C. After the heat curing treatment, the inside and outside of the vial container were washed three times with purified water, and then a 3% by mass concentration citric acid aqueous solution (adjusted to pH 8 with sodium hydroxide) was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then heat treatment was performed at 121°C for 180 minutes while preventing leakage of the internal liquid.
[0084] [Sample No. 15] The coating agent shown in Example 1 was applied to a vial containing 10 mL of solution processed from a borosilicate glass tube with an outer diameter of 22 mm and a wall thickness of 1 mm in the same manner, and heat curing treatment was performed for 30 minutes in a dryer heated to 275°C. After the heat curing treatment, the inside and outside of the vial container were washed three times with purified water, and then a glycine aqueous solution adjusted to 20 mM (pH 10 adjusted with sodium hydroxide) was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then heat treatment was performed at 121°C for 180 minutes while preventing leakage of the internal liquid.
[0085] [Sample No. 16] The coating agent shown in Example 1 was applied to a 10 mL solution vial processed from a borosilicate glass tube with an outer diameter of 22 mm and a wall thickness of 1 mm in the same manner, and heat curing treatment was performed for 30 minutes in a dryer heated to 275 ° C. After the heat curing treatment, the inside and outside of the vial container were washed three times with purified water, and then 50 mM phosphate buffer prepared using an aqueous solution of disodium hydrogen phosphate and an aqueous solution of sodium dihydrogen phosphate was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then heat treatment was performed at 121 ° C for 180 minutes while preventing leakage of the internal liquid.
[0086] [Sample No. 17] The coating agent shown in Example 1 was applied to a vial containing 10 mL of solution processed from a borosilicate glass tube with an outer diameter of 22 mm and a wall thickness of 1 mm in the same manner, and heat curing treatment was performed for 30 minutes in a dryer heated to 275°C. After the heat curing treatment, the inside and outside of the vial container were washed three times with purified water, and then 10% by mass of sodium thiosulfate (adjusted to pH 10 with sodium hydroxide) was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then heat treatment was performed at 121°C for 180 minutes while preventing leakage of the internal liquid.
[0087] [Sample No. 18] The coating agent shown in Example 1 was applied to a vial containing 10 mL of solution processed from a borosilicate glass tube with an outer diameter of 22 mm and a wall thickness of 1 mm in the same manner, and heat curing treatment was performed for 30 minutes in a dryer heated to 275°C. After the heat curing treatment, the inside and outside of the vial container were washed three times each with purified water, and then filled with 0.001 M hydrochloric acid aqueous solution up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then heat treatment was performed at 121°C for 180 minutes while preventing leakage of the internal liquid.
[0088] [Sample No. 19] The coating agent shown in Example 1 was applied to a 10 mL solution vial processed from a borosilicate glass tube with an outer diameter of 22 mm and a wall thickness of 1 mm in the same manner, and heat curing treatment was performed for 30 minutes in a dryer heated to 275°C. After the heat curing treatment, the inside and outside of the vial container were washed three times each with purified water, and then a 10% by mass concentration histidine aqueous solution was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then heat treatment was performed at 121°C for 180 minutes while preventing leakage of the internal liquid.
[0089] [Sample No. 20] A vial containing 10 mL of solution processed from a silicate glass tube with an outer diameter of 22 mmφ and a wall thickness of 1 mm was thinly and uniformly coated with a certain amount of the coating agent shown in Example 1 through a spray nozzle, and then the coated vial was subjected to a heat curing treatment for 30 minutes in a dryer heated to 275°C. After the heat curing treatment, the inside and outside of the vial were washed three times each with purified water, and then a 3% by mass concentration citric acid aqueous solution (adjusted to pH 8 with sodium hydroxide) was filled up to 90 volumes. Then, a rubber stopper and an aluminum cap were placed on the mouth of the vial and rolled up, and the internal liquid was prevented from leaking, and then heat treatment was performed at 121°C for 180 minutes.
[0090] [Sample No. 21] The coating agent shown in Example 1 was applied to a vial containing 10 mL of solution processed from a silicate glass tube with an outer diameter of 22 mm and a wall thickness of 1 mm in the same manner as in the case of sample No. 20, and heat curing treatment was performed for 30 minutes in a dryer heated to 275°C. After the heat curing treatment, the inside and outside of the vial container were washed three times each with purified water, and then a 3% by mass concentration citric acid aqueous solution (adjusted to pH 8 with sodium hydroxide) was filled up to 90 volumes. Then, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and the internal liquid was prevented from leaking, and heat treatment was performed at 121°C for 180 minutes.
[0091] [Sample No. 22] The coating agent shown in Example 1 was applied to a cycloolefin copolymer vial having an outer diameter of 22 mmφ and a wall thickness of 1 mm and a capacity of 10 mL in the same manner as in the case of sample No. 20, and heat curing treatment was performed for 10 minutes in a dryer heated to 185 ° C. After the heat curing treatment, the inside and outside of the vial container were washed three times with purified water, and then a 3% by mass concentration aqueous citric acid solution (adjusted to pH 8 with sodium hydroxide) was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then the internal liquid was prevented from leaking, and heat treatment was performed for 180 minutes at 121 ° C. After the heat treatment, the vial container was taken out, immersed in purified water, and cooled to room temperature.
[0092] [Sample No. 23-25] The coating agent shown in Example 1 was applied to a borosilicate glass container with an outer diameter of 22 mmφ, a wall thickness of 1 mm, and a capacity of 8 to 12 mL in the same manner as in the case of sample No. 20, and heat curing treatment was performed for 30 minutes in a dryer heated to 275 ° C. After the heat curing treatment, the inside and outside of the vial container were washed with purified water three times each, and then the purified water was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then the internal liquid was prevented from leaking, and heat treatment was performed at 121 ° C for 60 minutes. After the heat treatment, the vial container was taken out, immersed in purified water, and cooled to room temperature.
[0093] [Sample No. 26-28] The coating agent shown in Example 1 was applied to a borosilicate glass having an outer diameter of 22 mmφ and a wall thickness of 1 mm and a capacity of 8 to 12 mL in the same manner as in the case of sample No. 20, and heat curing treatment was performed for 30 minutes in a dryer heated to 275 ° C. After the heat curing treatment, the inside and outside of the vial container were washed three times with purified water, and then a citric acid aqueous solution with a concentration of 3% by mass (adjusted to pH 8 with sodium hydroxide) was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then the internal liquid was prevented from leaking, and heat treatment was performed for 180 minutes at 121 ° C. After the heat treatment, the vial container was taken out, immersed in purified water, and cooled to room temperature.
[0094] [Sample No. 29, 30] The coating agent shown in Example 1 was applied to a 5.5 mL borosilicate glass with an outer diameter of 16 mmφ and a wall thickness of 1 mm in the same manner as in the case of sample No. 20, and heat curing treatment was performed for 30 minutes in a dryer heated to 275 ° C. After the heat curing treatment, the inside and outside of the vial container were washed three times with purified water, and then a 3 mass % concentration citric acid aqueous solution (adjusted to pH 8 with sodium hydroxide) was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then the internal liquid was prevented from leaking, and heat treatment was performed at 121 ° C. for 60 minutes. After the heat treatment, the vial container was taken out, immersed in purified water, and cooled to room temperature.
[0095] [Sample No. 31, 32] The coating agent shown in Example 1 was applied to a 25 mL borosilicate glass with an outer diameter of 30 mmφ and a wall thickness of 1 mm in the same manner as in the case of sample No. 20, and heat curing treatment was performed for 45 minutes in a dryer heated to 275 ° C. After the heat curing treatment, the inside and outside of the vial container were washed three times with purified water, and then a 3 mass % concentration citric acid aqueous solution (adjusted to pH 8 with sodium hydroxide) was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then the internal liquid was prevented from leaking, and heat treatment was performed at 121 ° C. for 60 minutes. After the heat treatment, the vial container was taken out, immersed in purified water, and cooled to room temperature.
[0096] [Sample No. 33, 34] The coating agent shown in Example 1 was applied to a 35 mL borosilicate glass with an outer diameter of 30 mmφ and a wall thickness of 1 mm in the same manner as in the case of sample No. 20, and heat curing treatment was performed for 5 minutes in a dryer heated to 300 ° C. After the heat curing treatment, the inside and outside of the vial container were washed three times with purified water, and then a 3 mass % concentration citric acid aqueous solution (adjusted to pH 8 with sodium hydroxide) was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then the internal liquid was prevented from leaking, and heat treatment was performed at 121 ° C. for 60 minutes. After the heat treatment, the vial container was taken out, immersed in purified water, and cooled to room temperature.
[0097] [Sample No. 35-38] The coating agent shown in Example 1 was applied to a 60 mL borosilicate glass with an outer diameter of 30 mmφ and a wall thickness of 1 mm in the same manner as in the case of sample No. 20, and heat curing treatment was performed for 30 minutes in a dryer heated to 275 ° C. After the heat curing treatment, the inside and outside of the vial container were washed three times with purified water, and then a 3 mass % concentration citric acid aqueous solution (adjusted to pH 8 with sodium hydroxide) was filled up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and rolled up, and then the internal liquid was prevented from leaking, and heat treatment was performed at 121 ° C. for 60 minutes. After the heat treatment, the vial container was taken out, immersed in purified water, and cooled to room temperature.
[0098] [Sample No. 39] The inside and outside of a 12 mL borosilicate glass container with an outer diameter of 22 mm and a wall thickness of 1 mm were washed three times with purified water, and then the container was filled with purified water up to 90 volumes. After that, a rubber stopper and an aluminum cap were placed on the mouth of the vial container and the container was rolled up and then heat-treated at 121°C for 60 minutes while preventing leakage of the liquid. After the heat treatment, the vial container was removed, immersed in purified water, and cooled to room temperature.
[0099] Next, the vial containers after the heat treatment were evaluated for the following items (1) to (4).
[0100] (1) Recovery rate test The recovery rate test of purified water was carried out according to the following procedure. First, the vial container after the heating test was taken out, immersed in purified water, cooled to room temperature, washed with purified water, water droplets were removed, and the mass of the vial container was measured and recorded on an electronic balance. The mass was measured in a state where 8.8 mL of purified water was filled into the vial container, and the mass of the vial container was subtracted to calculate the "mass of filled purified water". The vial container filled with purified water was inverted, and the empty vial container after the purified water was discharged was placed on the electronic balance again, and the mass was measured and recorded. The "mass of recovered purified water" was calculated by subtracting the mass of the vial container after the water was discharged from the mass of the filled purified water. Finally, the recovery rate of the filled purified water was calculated using formula (1). Recovery rate (%) = {(mass of purified water recovered) / (mass of purified water filled)} × 100 (1)
[0101] (2) Water repellency test First, the vial container after the heating test was taken out, immersed in purified water, cooled to room temperature, washed with purified water, and then water droplets were removed. Next, the bottom area S cm 2 A volume of purified water V (ml) equivalent to 0.1 × 0.01 was dropped onto the bottom of the container, the container was turned left and right, then turned back to its original position, and the proportion of the bottom area S' covered by the purified water was measured when the container was placed again horizontally.
[0102] (3) External Observation For the appearance observation, the vial container filled with the solvent after the heating test was held up to a light source such as a fluorescent lamp to check for the presence of insoluble foreign matter in the solvent and for cracks or peeling of the coating layer. If no insoluble foreign matter or cracks or peeling of the coating layer were found, it was marked with a circle for "no appearance defect," and if only slight cracks were found, it was marked with a triangle for "slight appearance defect." If cracks were found, it was marked with an X for "present appearance defect."
[0103] (4) Si elution amount analysis For the analysis of the amount of silicon elution, the rubber stopper and aluminum cap were removed from the vial after the heating test, and the eluate in the vial was collected in a centrifuge tube.Then, the silicon concentration in the eluate was analyzed by ICP-OES.
[0104] (5) Measurement of coating layer thickness The thickness of the coating layer was measured by the following procedure. Scratches were made on the outer surface of the container body with a wheel glass cutter (Mitsuboshi Diamond Co., Ltd., Normal Wheel Type). The scratches were made in the longitudinal direction from the bottom to the shoulder of the container, dividing the circumference of the container into 6 or 8 equal parts. Scratches were also made radially on the outer surface of the bottom of the container, dividing the bottom into 6 or 8 equal parts. Next, a thickness of 100 mm was measured using a glass cutter with a thermal expansion coefficient of approximately 100×10 -7 One end of a soda-lime glass rod at 100 / °C was roasted with an oxygen gas burner to soften it. The container was held upside down by the mouth, and the softened glass rod was pressed against the scratched part on the side of the container and held there for a few seconds. The glass rod was repeatedly heated and pressed against the scratched part until a crack had developed from the shoulder to the bottom of the container. The crack was similarly propagated in another adjacent scratched part. Finally, the heated glass rod was pressed against the bottom of the container, and the crack was propagated radially. When the crack had mostly developed, the side and bottom of the container were struck to remove the side and bottom parts. The glass piece was set in a sample holder so that the cross section was facing up, and the cross section was observed using a high spatial resolution SEM SU8220 (Hitachi High-Technologies Corporation) to measure the thickness of the coating layer.
[0105] (6) Measurement of linear thermal expansion coefficient The linear thermal expansion coefficient was measured in a measurement temperature range of 30 to 380°C using a dilatometer.
[0106] Measurement means for clarifying the resin structure include an infrared spectroscopic analyzer (IR), Raman spectroscopy, etc. In this embodiment, Raman spectroscopy was used from the viewpoint of being able to detect resin structure information easily and with high accuracy. For the coating layers of Samples No. 2, 3, and 9, Raman spectra were measured using a laser Raman microscope RAMAMtouch (manufactured by Nanophoton Corporation). In detail, first, a vial container on which a coating layer was formed was broken, and a 532 nm laser beam was irradiated onto the inner surface of the container, and a pinhole or slit function was used to physically narrow the laser irradiation area so that Raman scattering was obtained only from minute, extremely thin parts, and a wavenumber range of 500 to 3500 cm was obtained. -1 The measurements were performed using a Gaussian function to perform peak fitting on each peak in the obtained Raman spectrum, and the ratio of the intensity of each peak when the obtained base value was set to 1 was calculated using formula (2). (Intensity of each peak) / (Base intensity obtained by fitting process) (2)
[0107] In addition, 1000 cm -1 Near and 1030cm -1 The peak at 1035 cm is due to the Si-O-Si stretching vibration. -1 In the vicinity, there is a peak due to the bending vibration of the C-H bond of the phenyl group, 1060 cm -1 Near and 1092cm -1 In the vicinity, there is a peak due to the deformation vibration of the CH bond of the methyl group, 1595 cm -1 In the vicinity, there is a peak due to the stretching vibration of the C=C bond of the phenyl group, 2910 cm -1 At 2970 cm, there is a peak due to the stretching vibration of the C-H bond of the phenyl group. -1 In the vicinity, there is a peak due to the antisymmetric stretching vibration of the C-H bond of the methyl group, 3055 cm -1 Peaks due to the stretching vibration of the C-H bond of the phenyl group appear in the vicinity.
[0108] As can be seen from Tables 1 to 4, Samples Nos. 1 to 4, 6, and 9 to 38 had better water repellency than Samples Nos. 5, 7, and 8. Therefore, it is possible that the rising of the formulation can be suppressed during the freeze-dried formulation process, and that defects in the appearance of the product can be reduced. In addition, Sample No. 25 had a smaller amount of Si elution than the uncoated Sample No. 39.
[0109] Table 5 shows an example of the present invention (sample No. 40) and a comparative example (sample No. 41).
[0110] [Table 5]
[0111] A coating agent was prepared by mixing and dissolving 30% by mass of an organopolysiloxane compound (silicone resin) containing methyl and phenyl groups, 15% by mass of butyl alcohol, 10% by mass of isopropyl acetate, and 45% by mass of isopropyl alcohol, and then adding 2% by mass of citric acid, mixing and dissolving the mixture. Note that the molar ratio of dimethylpolysiloxane, phenylpolysiloxane, and methylpolysiloxane contained in the organopolysiloxane compound was adjusted to 1.3:1:1.
[0112] [Sample No. 40] The coating agent was applied by spin coating onto a non-alkali aluminosilicate glass substrate (OA-10G manufactured by Nippon Electric Glass Co., Ltd.). The glass substrate with the coating agent applied was dried for 60 minutes in a dryer heated to 60°C. Next, a heat curing treatment was performed for 60 minutes in a dryer heated to 210°C to 225°C, forming a coating layer with a thickness of 1500 nm on the glass surface. The contact angle and transmittance (wavelength range 400 to 700 nm) of the glass substrate after the heat curing treatment were measured.
[0113] The contact angle was measured using a contact angle measuring instrument (Asumi Giken B100) and purified water. The transmittance was measured using a spectrophotometer (JASCO V-670). The measurement wavelength was 200-800 nm, the sampling pitch was 1 nm, the slit width was 5 nm, and the scan speed was 200 nm / min.
[0114] [Sample No. 41] The same glass substrate (OA-10G manufactured by Nippon Electric Glass Co., Ltd.) as that of Sample No. 40 was used, and the contact angle and transmittance (wavelength range 400 to 700 nm) were measured without forming a coating layer.
[0115] As can be seen from Table 5, sample No. 40 had better water repellency than sample No. 41. In addition, sample No. 40 had the same transmittance as sample No. 41.
Claims
1. A pharmaceutical container comprising at least a container and a coating layer, A coating layer is formed on at least the inner surface of the container, and the coating layer comprises a silicone-based resin, the silicone-based resin comprising an organopolysiloxane compound comprising dimethylpolysiloxane, phenylpolysiloxane, and methylpolysiloxane.
2. 2. The pharmaceutical container of claim 1, wherein the coating layer is substantially free of halogen components.
3. The pharmaceutical container according to claim 1 or 2, wherein the coating layer has a thickness of 10 to 2500 nm.
4. The container is made of silicate glass, The silicate glass has a glass composition, in mass%, of SiO 2 65-85%, Al 2 O 3 0-15%, B 2 O 3 0-13%, Li 2 O 0-5%, Na 2 O 3-15%, K 2 The pharmaceutical container according to any one of claims 1 to 3, containing 0-5% O, 0-5% MgO, 0-15% CaO, and 0-5% BaO.
5. The pharmaceutical container according to any one of claims 1 to 4, wherein the amount of silicon eluted when filled with purified water and subjected to a heat treatment at 121°C for 180 minutes is 40 µg / mL or less.
6. The pharmaceutical container according to any one of claims 1 to 4, wherein the amount of silicon eluted when filled with purified water and subjected to a heat treatment at 121°C for 180 minutes is 20 µg / mL or less.
7. The pharmaceutical container according to any one of claims 1 to 4, wherein the amount of silicon eluted when filled with purified water and subjected to a heat treatment at 121°C for 180 minutes is 15 µg / mL or less.
8. The pharmaceutical container according to any one of claims 1 to 7, wherein when the amount of Si eluted is X μg / mL and the thickness of the coating layer is Y nm when the pharmaceutical container is filled with a 3 mass% citric acid aqueous solution having a pH of 8 and heat-treated at 121 ° C. for 180 minutes, the relationship of X / Y≦10 is satisfied.
9. The pharmaceutical container according to any one of claims 1 to 7, wherein when the amount of Si eluted is X μg / mL and the thickness of the coating layer is Y nm when the container is filled with a 3 mass% citric acid aqueous solution having a pH of 8 and heat-treated at 121 ° C. for 180 minutes, the relationship X / Y≦7 is satisfied.
10. The pharmaceutical container according to any one of claims 1 to 7, wherein when the amount of Si eluted is X μg / mL and the thickness of the coating layer is Y nm when the pharmaceutical container is filled with a 3 mass% citric acid aqueous solution having a pH of 8 and heat-treated at 121 ° C. for 180 minutes, the relationship X / Y≦5 is satisfied.
11. Container bottom area S cm 2 A volume (ml) of purified water equivalent to 0.1 x 0.1 is dropped onto the bottom of the container, the container is turned left and right, then turned upright and placed horizontally. The bottom area S' covered by the purified water when the container is placed horizontally is calculated as the bottom area S cm 2 The pharmaceutical container according to any one of claims 1 to 10, wherein the viscosity is 90% or less.
12. Container bottom area S cm 2 A volume (ml) of purified water equivalent to 0.1 x 0.1 is dropped onto the bottom of the container, the container is turned left and right, then turned upright and placed horizontally. The bottom area S' covered by the purified water when the container is placed horizontally is calculated as the bottom area S cm 2 The pharmaceutical container according to any one of claims 1 to 10, wherein the viscosity is 85% or less.
13. Container bottom area S cm 2 A volume (ml) of purified water equivalent to 0.1 x 0.1 is dropped onto the bottom of the container, the container is turned left and right, then turned upright and placed horizontally. The bottom area S' covered by the purified water when the container is placed horizontally is calculated as the bottom area S cm 2 The pharmaceutical container according to any one of claims 1 to 10, wherein the viscosity is 80% or less.
14. A container comprising at least a coating layer, A coating layer is formed on at least the inner surface of the container, The coating layer comprises a silicone-based resin, and the silicone-based resin comprises an organopolysiloxane compound including dimethylpolysiloxane, phenylpolysiloxane, and methylpolysiloxane; Container bottom area S cm 2 A volume (ml) of purified water equivalent to 0.1 x 0.1 is dropped onto the bottom of the container, the container is turned left and right, then turned upright and placed horizontally. The bottom area S' covered by the purified water when the container is placed horizontally is calculated as the bottom area S cm 2 90% or less of the container.
15. Container bottom area S cm 2 A volume (ml) of purified water equivalent to 0.1 x 0.1 is dropped onto the bottom of the container, the container is turned left and right, then turned upright and placed horizontally. The bottom area S' covered by the purified water when the container is placed horizontally is calculated as the bottom area S cm 2 15. The container of claim 14, wherein the container has a thickness of 85% or less.
16. A method for producing a pharmaceutical container comprising at least a container and a coating layer, comprising: Providing a container made of silicate glass or resin; applying a coating agent to at least the inner surface of the container, the coating agent including a silicone-based resin and an organopolysiloxane compound including dimethylpolysiloxane, phenylpolysiloxane, and methylpolysiloxane; and a step of thermally curing the applied coating agent to form a coating layer.
17. The method for producing a pharmaceutical container according to claim 16, wherein the coating agent comprises an organic acid.
18. The method for producing a pharmaceutical container according to claim 16 or 17, wherein the organic acid is one or more selected from the group consisting of an amino acid, citric acid, acetic acid, and oxalic acid.
19. The method for producing a pharmaceutical container according to any one of claims 16 to 18, wherein the coating layer has a thickness of 10 to 2500 nm.
20. A coating agent for forming a coating layer on a glass surface or a resin surface. A coating agent comprising organopolysiloxane compounds including dimethylpolysiloxane, phenylpolysiloxane and methylpolysiloxane.
21. A coating agent for forming a coating layer on an inner surface of a pharmaceutical container, A coating agent comprising organopolysiloxane compounds including dimethylpolysiloxane, phenylpolysiloxane and methylpolysiloxane.
22. 22. The coating agent according to claim 20 or 21, which is substantially free of halogen components.
23. The coating agent according to any one of claims 20 to 22, wherein the content of the organopolysiloxane compound is 1 to 50 mass%.
24. The coating agent according to claim 20, wherein, when the molar ratios of dimethylpolysiloxane:phenylpolysiloxane:methylpolysiloxane are A:B:C, A is 0.1 to 4.0, B is 0.1 to 4.0, and C is 0.1 to 4.
0.
25. The coating agent according to any one of claims 20 to 24, further comprising one or more organic acids selected from the group consisting of citric acid, amino acids, acetic acid, and oxalic acid.
26. The coating agent according to claim 25, wherein the content of the organic acid is 0.1 to 10% by mass.
Citation Information
Patent Citations
Surface-treated glass bottle
JP1993132065A
Lyophilized preparation using silica-coated container
JP1996175998A
Coating film having low refractive index and water repellency
JP1997208898A
Organopolysiloxane mixture composition, filler-containing organopolysiloxane, coating material, and coated body
JP2013203989A
Glass containers with improved strength and improved damage resistance
JP2016505455A